2017
DOI: 10.1016/j.jtumed.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional education and practice in an Indian setting

Abstract: With current global healthcare trends, there is a growing need for interprofessional education (IPE) and interprofessional practice (IPP) in collaborative care of persons with chronic medical conditions. Tools and models for IPE and IPP are now available, but they are not yet in widespread use. Developmental-behavioural paediatrics is a medical discipline that is characterized by IPP with an encouraging emergence of this speciality in India and other developing countries. This article provides an overview of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…So, the innate desire to familiarise oneself with the working of other healthcare courses already exists in most of the students. This study confirms the literature findings of positive interprofessional learning behaviour among other healthcare students 9,11,14,23 . This result was also similar to various reported studies on students of different health disciplines in different countries 17,21 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…So, the innate desire to familiarise oneself with the working of other healthcare courses already exists in most of the students. This study confirms the literature findings of positive interprofessional learning behaviour among other healthcare students 9,11,14,23 . This result was also similar to various reported studies on students of different health disciplines in different countries 17,21 .…”
Section: Discussionsupporting
confidence: 92%
“…Educational institutions and academia uphold a critical role in inculcating the core components of successful health practices as well as learning across disciplines. Many universities in North America like University of Colorado, University of South Carolina, Columbia University, University of Florida and University of Minnesota are currently offering IPE as an elective or as a mandatory inclusion in the curriculum 12,13 whereas in Asian countries, particularly in India, this has not yet been implemented by the Universities 14 …”
Section: Introductionmentioning
confidence: 99%
“…Developmental-behavioural paediatrics is currently being recognized as a subspecialty of paediatrics and is well-established in many developed countries. The training programmes provided aim to increase the number of providers who engage in IPP and establish themselves at providing specialised care 21 . This, however, remains a new and emergent subspecialty in India.…”
Section: Importance Of Proposed Researchmentioning
confidence: 99%
“…Although reviews showed that awareness of IPE was average among the students, majority had good knowledge and a positive perception 7,8,9,10,11,12,13,14 . Literature also had recommended the need to improve their awareness and knowledge about IPE by making use of combined seminars for the various healthcare professional novices and also by implementing IPE into their present curricula of training 15,16,17,18,19,20,21,22,23,24 .…”
Section: Introductionmentioning
confidence: 99%
“… 8 Implementation of IPE in the Asian context, including its effectiveness and challenges, has been previously reported. 9 13 …”
Section: Introductionmentioning
confidence: 99%